Knowledge, Attitude, and Willingness to Perform Basic Life Support among Online Motorcycle Taxi Drivers - Raisa Salsabila; Eka Yulia Fitri; Mutia Nadra Maulida (Indonesian Journal of Global Health Research, 2025)
Cardiac arrest is one of the emergency conditions that can occur anywhere and can result in death if not treated immediately. Handling cardiac arrest can be done by providing basic life support by the community, including online motorcycle taxi drivers. Knowledge, attitudes and willingness of helpers in performing basic life support measures are needed to reduce the risk of death in victims of cardiac arrest. Objective: This research aims to determine the level of knowledge, attitudes, and willingness to perform basic life support among online motorcycle taxi drivers in Palembang city. Methods: A quantitative methods using descriptive study approach was conducted at Palembang City, South Sumatera, Indonesia in 2023. In this study, 106 online motorcycle taxi drivers were assigned using accidental sampling. The knowledge, attitude, and willingness to perform basic life support was assessed using a questionnaire. A descriptive analysis was conducted to describe the frequency and percentages of the variables. Results: The results showed that 46.2% of respondents had sufficient knowledge, 54.7% of respondents had a positive attitude, and 95.3% of respondents had a willingness to perform cardiopulmonary resuscitation to immediate family members and relatives. The main factors of unwillingness to perform cardiopulmonary resuscitation were the situation of the victim (42.5%). Conclusion: Not all respondents have good knowledge, positive attitudes and willingness to perform cardiopulmonary resuscitation, so a strategy is required to provide basic life support education and training to the community.